2022
DOI: 10.5194/gmd-15-395-2022
|View full text |Cite
|
Sign up to set email alerts
|

Coupling the Community Land Model version 5.0 to the parallel data assimilation framework PDAF: description and applications

Abstract: Abstract. Land surface models are important for improving our understanding of the Earth system. They are continuously improving and becoming better in representing the different land surface processes, e.g., the Community Land Model version 5 (CLM5). Similarly, observational networks and remote sensing operations are increasingly providing more data, e.g., from new satellite products and new in situ measurement sites, with increasingly higher quality for a range of important variables of the Earth system. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…The scatter plot for Wüstebach in Figure A3 indicates that modeled soil moisture updates reach an upper plafond, which is defined by the maximum possible porosity in the model, which is determined by the soil texture and pedotransfer function. However, the remarkably high porosity of the forest soil is due to the very high content of organic material in the topsoil, so the real porosity of Wüstebach cannot be represented in the model by the soil texture alone (Strebel et al., 2022). Therefore, the upper porosity limit inhibits further improvement of soil moisture characterization.…”
Section: Resultsmentioning
confidence: 99%
“…The scatter plot for Wüstebach in Figure A3 indicates that modeled soil moisture updates reach an upper plafond, which is defined by the maximum possible porosity in the model, which is determined by the soil texture and pedotransfer function. However, the remarkably high porosity of the forest soil is due to the very high content of organic material in the topsoil, so the real porosity of Wüstebach cannot be represented in the model by the soil texture alone (Strebel et al., 2022). Therefore, the upper porosity limit inhibits further improvement of soil moisture characterization.…”
Section: Resultsmentioning
confidence: 99%
“…The reference simulations showed higher correlations between the simulated and observed surface soil moisture 540 than the forecast experiments, which could be expected given the wrong timing of precipitation events in the seasonal weather predictions, while still showing similar systematic differences compared to all products. Earlier studies with CLM3.5 (e.g., Zhao et al, 2021;Hung et al, 2022) and CLM5 (e.g., Strebel et al, 2022) found pronounced discrepancies in CLM-simulated soil moisture contents and field measurements. In this context, data assimilation has proven to be a valuable technique to reproduce better soil moisture dynamics (Strebel et al, 2022).…”
Section: Regional Crop Yield Predictionsmentioning
confidence: 90%
“…Earlier studies with CLM3.5 (e.g., Zhao et al, 2021;Hung et al, 2022) and CLM5 (e.g., Strebel et al, 2022) found pronounced discrepancies in CLM-simulated soil moisture contents and field measurements. In this context, data assimilation has proven to be a valuable technique to reproduce better soil moisture dynamics (Strebel et al, 2022). 545…”
Section: Regional Crop Yield Predictionsmentioning
confidence: 90%
See 2 more Smart Citations